Identifying Coping Strategies for Managing Intergenerational Tensions in Multigenerational Households - Wong, Yoko; Sun, Jing (Journal of Psychosociological Research in Family and Culture, 2025)
Objective: This study aims to explore the coping strategies employed by individuals in multigenerational households to manage intergenerational tensions. Methods and Materials: This qualitative study utilized a phenomenological approach to examine the lived experiences of individuals residing in multigenerational households. Data were collected through semi-structured interviews with 22 participants recruited via online platforms, ensuring diverse perspectives on intergenerational conflict resolution. The study employed a purposive sampling strategy, and interviews continued until theoretical saturation was achieved. NVivo software was used to facilitate thematic analysis, allowing for systematic identification of key coping mechanisms. The analysis involved open coding, axial coding, and thematic categorization to identify patterns and relationships within the data. Findings: The thematic analysis revealed four major coping strategies: (1) communication strategies, including active listening, conflict mediation, humor, and digital communication adaptation; (2) emotional regulation techniques, such as emotional distancing, cognitive reframing, mindfulness, seeking social support, and expressing gratitude; (3) household management strategies, including role negotiation, financial contributions, time management, privacy arrangements, and household meetings; and (4) interpersonal adaptation, which encompassed respecting autonomy, negotiating values, engaging in intergenerational bonding activities, and encouraging mutual learning. The findings indicate that multigenerational households actively develop adaptive mechanisms to mitigate conflicts and enhance familial cohesion. Conclusion: The results underscore the importance of structured communication, emotional regulation, and adaptive household management in fostering harmony in multigenerational households. The study contributes to the existing literature by highlighting practical coping strategies that facilitate positive intergenerational relationships and reduce conflict. These insights can inform interventions aimed at improving household dynamics through counseling, policy initiatives, and targeted support programs.